2017
DOI: 10.1007/s11030-017-9782-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel quinazolin-4(3H)-one derivatives containing the 7-oxo-1,2,4-triazolo[1,5-a]pyrimidine moiety as effective agricultural bactericides against the pathogen Xanthomonas oryzae pv. oryzae

Abstract: A series of novel quinazolin-4-one derivatives (7a-7n) bearing the 7-oxo-1,2,4-triazolo[1,5-a]pyrimidine moiety were designed, synthesized and evaluated for their inhibition activities against phytopathogenic bacteria and fungi in vitro. All of the target compounds were fully characterized through [Formula: see text] NMR, [Formula: see text] NMR, HRMS and IR spectra. Among these compounds, the structure of compound 7e was unambiguously confirmed via single-crystal X-ray diffraction analysis. The turbidimetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Triazole derivatives have attracted considerable interest in the scientific community due to their vast range of biological activities. In addition to antifungal action [ 14 , 15 , 16 , 17 , 18 , 19 ], they were shown to possess other antimicrobial effects such as antibacterial, including anti-tuberculous activity [ 20 , 21 , 22 , 23 , 24 ], antiparasitic [ 25 , 26 , 27 ] and anti-HIV effects [ 28 ] as well as anticholinesterase [ 29 ], antiangiogenic [ 30 ], anticancer [ 31 , 32 ], antidiabetic [ 33 , 34 ] and anticonvulsant activities [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Triazole derivatives have attracted considerable interest in the scientific community due to their vast range of biological activities. In addition to antifungal action [ 14 , 15 , 16 , 17 , 18 , 19 ], they were shown to possess other antimicrobial effects such as antibacterial, including anti-tuberculous activity [ 20 , 21 , 22 , 23 , 24 ], antiparasitic [ 25 , 26 , 27 ] and anti-HIV effects [ 28 ] as well as anticholinesterase [ 29 ], antiangiogenic [ 30 ], anticancer [ 31 , 32 ], antidiabetic [ 33 , 34 ] and anticonvulsant activities [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Appearing fine effects on antimalarial, antifungal, anti‐obesity, anticancer, antibacterial, anti‐flammatory, insecticidal and vasorelaxant activities, natural quinazolin‐4(3 H )‐ones show important applications and development perspectives in searching for bioactive lead compounds . Further investigations on the structural optimization of quinazolin‐4(3 H )‐ones found that introducing Schiff base, amide, 1,2,4‐triazole,, 1,2,4‐triazolo[3,4‐ b ][1,3,4]thiadiazole and 1,2,4‐triazolo[1,5‐ a ]pyrimidine scaffolds at the N ‐3 position of quinazolin‐4(3 H )‐one could greatly enhance and broaden their antimicrobial activities. Strikingly, Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this class of compounds did not display inhibition activity against three fungi tested. The above findings indicated that quinazolin-4-one derivatives containing the 7-oxo-1,2,4-triazolo [1,5-a]pyrimidine moiety have a potential as promising candidates for the development of new and more efficient agricultural bactericides 14 .…”
Section: Triazol Derivativesmentioning
confidence: 88%